Kwanzaa - Tyner, Artika R. (2022)
"Kwanzaa is about celebrating! It honors African American heritage. Some people mark the holiday by lighting the kinara. Families and friends gather to eat a big feast. Readers will discover how a shared holiday can have multiple traditions and be celebrated in all sorts of ways"--
Includes bibliographical references and index.
Ages 5-8
Grades K-1
Keywords: Kwanzaa -- Juvenile literature; African Americans -- Social life and customs -- Juvenile literature; Holidays -- Juvenile literature